Pelaksanaan Bina Iman Anak Katolik (BIAK) Dalam Kegiatan Weekend Pastoral - Yuliana Eni Yuliati; Maria Vianti Desa (Jurnal Pelayanan Pastoral, 2020)
In weekend pastoral activities, students are directly involved in the life of the people of faith, including in the Catholic Children Community Development (BIAK). The goal to be achieved is to find out the role of weekend pastoral ministers in the implementation of Catholic Children Faith (BIAK) catechesis in St. Vincentius a Paulo parish, Malang. The research method used in this research is a qualitative descriptive approach with 3 groups of informants, namely the learders of communities, BIAK coaches and weekend pastoral ministers. The results showed that 8 out of 9 communities have BIAK groups and only 1 community does not have a BIAK group. All weekend pastoral ministers play roles in assisting the BIAK groups. They assist the BIAK group to be more creative and energetic, especially in terms of songs. They bring preparations before teaching, bring the necessary tools, so that the implementation of BIAK coaching is more creative and enjoyable.